2020
DOI: 10.1136/jitc-2020-001193
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based extracellular matrix biomarkers are correlated with clinical outcome after PD-1 inhibition in patients with metastatic melanoma

Abstract: BackgroundImmune checkpoint inhibitors that target the programmed cell death protein 1 (PD-1) receptor induce a response in only a subgroup of patients with metastatic melanoma. Previous research suggests that transforming growth factor beta signaling and a collagen-rich peritumoral stroma (tumor fibrosis), may negatively interfere with the interaction between T cells and tumor cells and thereby contribute to resistance mechanisms by immune-exclusion, while increased tumor infiltration of M1-like macrophages e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…MMP generated collagen fragments are abundant in cancer and correlate with poor prognosis (20,21). Collagen fragments also seem to contribute to therapeutic resistance since high levels of C1M in the circulation associate with poor response to anti-CTLA-4 therapy (22), and increased collagen turnover is associated with poor survival after anti-PD-1 therapy (42). Furthermore, LAIR-1-collagen interaction has been implicated in mediating resistance to current anti-PD-1 immunotherapy (26).…”
Section: Discussionmentioning
confidence: 99%
“…MMP generated collagen fragments are abundant in cancer and correlate with poor prognosis (20,21). Collagen fragments also seem to contribute to therapeutic resistance since high levels of C1M in the circulation associate with poor response to anti-CTLA-4 therapy (22), and increased collagen turnover is associated with poor survival after anti-PD-1 therapy (42). Furthermore, LAIR-1-collagen interaction has been implicated in mediating resistance to current anti-PD-1 immunotherapy (26).…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in this review, collagen could be a novel target for improving the efficacy of immunotherapies such as checkpoint inhibitors (74,(175)(176)(177)(178)(179)(180), TIL-based therapy (181), and cancer vaccines (182). The hypothesis that collagen in the tumor microenvironment can affect the outcome of cancer immunotherapy is supported by studies that have identified the serum level of the N-terminal pro-peptide of collagen type III (PRO-C3) as a marker of poor prognosis following anti-CTLA-4 and anti-PD-1 checkpoint inhibitor therapy in metastatic melanoma patients (183,184). This serum marker is believed to reflect the presence of a highly collagen-dense tumor microenvironment (185).…”
Section: The Effects Of Tumor Collagen On Immunotherapymentioning
confidence: 99%
“…In patients with stage IV melanoma, collagen-derived biomolecules RO-C3, C1M, C3M, and C4M are biomarkers of poor response to the therapy with immune checkpoint inhibitor (ICI) ipilimumab (42). In patients with metastatic melanoma, blood-based biomarkers of type III collagen turnover are associated with worse overall survival and progress-free survival following PD-1 inhibition immunotherapy (43). In a clinical scenario, the ECM-turnover associated with the response of melanoma to immuno-therapy might be assessed in a "liquid biopsy" (44), and allows to stratify patients with metastatic melanoma according to their response to ICI therapy (45).…”
Section: Ecm Components As Cancer Biomarkersmentioning
confidence: 99%
“…Aforementioned, many soluble ECM-derived molecules arising from within a solid tumor can be found in a peripheral blood, are detectable using routine laboratory methods such as immunoassays (42,43), and may therefore be used as a noninvasive "liquid biopsy" biomarkers. This makes them very attractive for use in clinics (47), the only limitation of their use being sensitivity and specificity of the immunoassay.…”
Section: Ecm Components As Cancer Biomarkersmentioning
confidence: 99%